2018
DOI: 10.1007/s00192-018-3727-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes of synthetic tape and mesh revision surgeries: a monocentric experience

Abstract: Although most symptoms resolved after tape and mesh surgical revisions, patients must be informed that symptoms may persist. Recurrent or persistent SUI or POP may require a subsequent surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The treatment of mesh exposure secondary to mid-urethral sling operations is partial or total removal of the mesh (16). However, various studies have reported that SUI recurs in approximately 30-60% of patients following the removal of the mesh (17). Jonathan et al (18) reported the results of 102 patients who underwent revision due to mesh erosion.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of mesh exposure secondary to mid-urethral sling operations is partial or total removal of the mesh (16). However, various studies have reported that SUI recurs in approximately 30-60% of patients following the removal of the mesh (17). Jonathan et al (18) reported the results of 102 patients who underwent revision due to mesh erosion.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients may have no symptoms, so a careful vaginal examination is needed after surgery for follow-up. Vaginal tape erosion without other problems can be treated in a conservative way, such as prointravaginal estrogen administration [5,11]. When conservative treatments fail, partial or complete tape removal is recommended [5,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal tape erosion without other problems can be treated in a conservative way, such as prointravaginal estrogen administration [5,11]. When conservative treatments fail, partial or complete tape removal is recommended [5,11,12]. For the correction of recurrent SUI, retropubic TVT tape is recommended for high priority with encouraging success [13].…”
Section: Discussionmentioning
confidence: 99%
“…Again, there is little guidance to determine the amount of mesh to be excised; among patients with reoperation for MUS-related pain, partial versus complete vaginal excision yielded similar rates of pain resolution (72%-76%) and the rates of SUI (22% for partial, 56% for complete) were not statistically significantly different [15]. It is important for the patient to realize that most data suggest that some degree of pain remains for onequarter to one-half of patients [30][31][32].…”
Section: Pain Associated With Musmentioning
confidence: 99%